Love yourself : her (korea : LOEN Entertainment., 2017)
The new album by BTS (Bangtan Boys) has been described as "a dual exploration of the group's electro-pop and hip-hop leanings", with the first half consisting of "dance tracks that emphasize the group's vocals" while in the second half "the act's hip-hop side arrives in earnest ... delivering powerful rap performances."
2017
LOEN Entertainment.
Keywords: K-pop (Music).